Comparative analysis on EPF investors’ knowledge, experience, and behaviour towards investing in Islamic and conventional unit trusts : the case of Malaysia - Md, Abu Hasnat; Che Mohd Salleh, Marhanum (Islamic Bank Training and Research Academy (IBTRA) of Islamic Bank Bangladesh Limited (IBBL), 2018)
The study explores EPF investors’ knowledge, experience and behavior towards investing in Islamic and conventional unit trusts in Malaysia. 110 valid responses were collected through surveys among government and private employees residing in Klang Valley area. Based on Statistical Package for Social Sciences (SPSS), it is found that majority of the respondents have enough knowledge about Islamic and conventional unit trusts while they have more experiences with the Islamic unit trust compared to the conventional. With regards to the EPF investors’ behaviour, most of them are heavily relied on various source of information to make decision on investing in the Islamic unit trust. Results of this research is very significant to proof that besides other sources of information, knowledge on both Islamic and conventional unit trust is relevant to make decision for future financial planning.